An investigation of occupational segragation in radio sport journalism. - Baxter, Lucy. (University of Ottawa (Canada), 1994)
The present study was an investigation of the occupational structure of a national sport department in a public corporation. The goal was to determine whether occupational segregation was occurring, and if so what were the processes underlying this situation. Questionnaires were administered to the personnel of a public radio station (n = 23) and subsequently interviews (n = 14) were conducted with a sample of personnel from the department, including the positions of reporter, producer, executive producer and manager. Official documents, particularly those concerning employment equity from the CRTC, were also analyzed. It was found that occupational segregation is occurring in this department, both vertically and horizontally. The dual queue theory was adopted to explain the labour market dynamics operating to perpetuate differential employment opportunities for men and women in radio sport journalism. It was discovered that although highly qualified white women are currently at the top of this particular labour queue, it is mainly a result of pressure from two main factors: the fact that it is a public company regulated by the CRTC, and the move on the part of the personnel from jock journalism to investigative sport journalism. Barriers operating to perpetuate the fact that women do not consider sport journalism as a viable career opportunity include lack of access, lack of work experience, the jock environment, stereotyping, power dynamics, lack of sporting contacts and networks, lack of mentoring or training programs. Processes occurring to reduce women's access to radio sport journalism are contextualized within the wider society, and recommendations are made, including one emphasizing the necessity to conduct an industry-wide analysis of employment opportunities for men and women in the sport media.
Keywords: Journalism.